Leading Sector Analysis of Regional Economic Growth - Syamsu Rijal (International journal of technology and education research, 2025)
This research aims to analyze the influence of leading sectors on regional economic growth in Makassar City during the 2015-2020 period. The leading sectors analyzed include the processing industry sector, wholesale and retail trade, and the tourism sector. This research uses quantitative methods with a descriptive approach and multiple linear regression to determine the relationship between leading sectors and economic growth. The data used in this research is secondary data obtained from the Central Statistics Agency (BPS) and other related agencies in Makassar City. The results of the analysis show that the processing industry sector has a significant and positive influence on regional economic growth. The wholesale and retail trade sectors also show a positive contribution but are not statistically significant. Meanwhile, the tourism sector shows a significant positive influence on economic growth. Overall, this research finds that the development of certain leading sectors can encourage regional economic growth in Makassar City. Therefore, it is recommended that local governments continue to strengthen and develop these sectors through appropriate policies and investments. Apart from that, economic diversification also needs to be considered to ensure the sustainability of regional economic growth in the long term.